Diseño y evaluación energética de un gasificador de combustible tipo Pantone acoplado a un grupo electrógeno de 2.5 kW de potencia eléctrica. - Pullaguari Infante, Estuardo Gustavo (2014)
The execution of this research project was born of the necessity of verify the hypothesis that there are about the operation of the Pantone system. First, the bibliographical gathering was taken account to know the operation and the finality that this system has when it couples to a motor of internal combustion. After that, it developed the recognition of the material that are used to the construction of the system, as well as the type of the machine which is going to be implemented in this system, choosing a electrogeno group of 2.5 kW of electric power. Previously, the entrance and exit variables were defined which are going to register and acquire the necessary equipments to realize the mensuration. Then, the operative data of the electrogeno group , working of formal way with a load constant, which would serve of reference in order to compare with the results that would have in the Pantone`s system. Also, the exploratory tests were carried on to verify the operation of the system in order to define the parameters that impact in the operation and carry on the experimentation. In this context, it is sought to study the problematic associated to the use of the motors of intern combustion in the generation of the energy and the decrease of the energetic resources. Therefore, this work sought to impel the benefits of technologies as the Pantone`s system that help to use of a way more reasonable the energetic resources.